Immunohistochemical detection of naturally occurring porcine Sapelovirus infection in Indian pigs. Issue 6 (2nd November 2019) - Kumari, Swati; Saikumar, G.; Desingu, P.A.; Das, T.; Singh, Rahul
ABSTRACT: We investigated immunohistochemical detection of porcine Sapelovirus (PSV) in naturally infected pigs of different ages. Forty-nine fecal samples, intestinal contents and other tissue samples from dead pigs were screened in previous study using reverse transcription polymerase chain reaction (RT-PCR) for PSV infection. Eight animals were positive for PSV based on RT-PCR examination. Gross lesions were recorded mainly in the large and small intestines. Microscopic examination of intestines showed severe enteritis. Tissue sections of all organs from PSV positive animals were immunostained using hyperimmune serum raised in rats against PSV that had been grown in a BHK-21 cell line. Staining of PSV was found only in the large and small intestines.